IMPACT OF DEVASTATING EARTHQUAKES IN CROATIA IN 2020 - Uroš, Mario; Atalić, Josip; Demšić, Marija; Baniček, Maja; Šavor Novak, Marta; Kadić, Alen (Journal of Applied Engineering Science, 2024)
At the beginning of 2020, the area of Zagreb was hit by an earthquake of magnitude Mw5.4, where a significant number of buildings in the historic core of the city was damaged. Not long after that, at the end of the same year, a strong earthquake of magnitude Mw6.4 hit the area of Sisak-Moslavina County, which is about 50 km away from Zagreb. It was a significantly stronger earthquake that had enormous consequences for that region and much wider. Earthquakes struck during the Covid-19 pandemic and shocked the whole country. This multi-hazard scenario surprised everybody, as the country was not ready. Regardless, in the first hours after the earthquake, a system of damage assessment was established based on experts from the academic and professional community, which would later grow into Croatian Centre for Earthquake Engineering. From a technical point of view, this paper refers to the response of the system to the earthquakes, post-earthquake activities of Croatian Centre for Earthquake Engineering and with challenges and problems in organization of damage inspection of the buildings. The paper briefly describes the earthquake scenarios in Zagreb and Petrinja. The typical vulnerable buildings typology and damage are described, trying to find explanations and guidelines for the future earthquakes. The focus is on the unreinforced masonry buildings and out of plane failures which prevail in damage, especially in historical buildings of cultural heritage. Such significant damage to buildings of historical importance makes us think about the way of their future protection and restoration that will follow. Also, some positive experiences in construction practice are highlighted. At the end, a perspective is given for the further development and improvement of the post-earthquake response system, and the need for cooperation of several professions is highlighted in order to obtain a synchronized response to earthquakes. In addition, international cooperation in the organization of the system before and after the earthquake is of key importance.